Modification of glass screen printed electrodes with graphene quantum dots for enhanced power output in miniaturized microbial fuel cells - Yuvraj Maphrio Mao; Khairunnisa Amreen; Rajnish Kaur Calay; Aritro Banerjee; Sanket Goel (Scientific Reports)
Abstract This paper demonstrates screen-printing technique, Glass Screen printed (GSP) on glass layer with Graphene Quantum Dots (GQDs) via drop casting approach to manufacture electrodes for Miniaturized Microbial Fuel Cells (MMFCs). MMFCs are viable options to sustainably operate low-power devices such as sensors, implantable medical devices, etc. However, the technology is still not fully mature for practical applications due to limitations of output power. Materials and design improvements are required for decreasing internal resistance for better electron transfer and improving overall performance. In this work the electrodes manufactured by GSP technique, and anode modified by GQD was tested in MMFC using RO wastewater. It was found that the GQDs increased the surface area to improve electron transfer kinetics at the anode. As a result, GQDs-based GSPEs showed 7.4 times higher power output 332 nW/cm2 compared to its unaltered electrode which displayed a power output of 44.8 nW/cm2. Electrodes made by GSP technique are more durable and less susceptible to biofouling and corrosion compared to conventional methods. The modified anodes further showed sustained output for long term operation.